Research on Comprehensive Evaluation of Water Ecological Environment in Small Basin. Issue 1 (January 2021) - Gao, Hua; Chu, Rui
Abstract: In order to evaluate the water ecological environment quality of small basin and realize scientific management and control of small basin, 15 sampling spots were set up on the small basin of Nanhe River of Qionglai city, 11 indexes were selected from three aspects of water environmental quality, aquatic ecology and aquatic habitat for each sampling spot, and the grey relational analysis (GRA) was used to comprehensively evaluate the water ecological environment quality in the small watershed of Nanhe River of Qionglai city. The results show that it is feasible to use GRA to comprehensively evaluate the regional water ecological environment. The water ecological environment of wenjing River, Baimo River and Dengjiang River is in good condition, and their control standards should be relatively improved. The water ecological environment of the five reaches of Xiaonan River, Shitou River, Pujiang River, Inclined River and the lower reaches of Nanhe River is in poor condition, which requires priority control. Pollution prevention and control measures should be considered comprehensively in combination with the ecological environmental pressure borne by the reach.